Frequency, severity and causes of unexpected allergic reactions to food: a systematic literature review. Issue 2 (February 2015) - Versluis, A.; Knulst, A. C.; Kruizinga, A. G.; Michelsen, A.; Houben, G. F.; Baumert, J. L.; van Os‐Medendorp, H.
Summary Food allergic patients have to deal with an avoidance diet. Confusing labelling terms or precautionary labels can result in misinterpretation and risk‐taking behaviour. Even those patients that strictly adhere to their diet experience (sometimes severe) unexpected allergic reactions to food. The frequency, severity and causes of such reactions are unknown. The objective of this review was to describe the frequency, severity and causes of unexpected allergic reactions to food in food allergic patients aged > 12 years, in order to develop improved strategies to deal with their allergy. A systematic review was carried out by two researchers, in six electronic databases (CINAHL, Cochrane, EMBASE, Medline, Psychinfo and Scopus). The search was performed with keywords relating to the frequency, severity and causes of unexpected allergic reactions to food. This resulted in 24 studies which met the inclusion criteria; 18 observational and six qualitative studies. This review shows that knowledge about the frequency of unexpected reactions is limited. Peanut, nuts, egg, fruit/vegetables and milk are the main causal foods. Severe reactions and even fatalities occur. Most reactions take place at home, but a significant number also take place when eating at friends' houses or in restaurants. Labelling issues, but also attitude and risky behaviour of patients can attribute to unexpected reactions. We conclude that prospective studies are needed to get more insight in the frequency, severity, quantity of unintended allergen ingested and causes of unexpected allergic reactions to food, to be able to optimize strategies to support patients in dealing with their food allergy. Although the exact frequency is not known, unexpected reactions to food occur in a significant number of patients and can be severe. For clinical practice, this means that patient education and dietary instructions are necessary.